Spatial-controlled nanoengineered films prepared via rapid catalyst induced cross-linking. Issue 19 (19th April 2016) - Nam, Eunhyung; Wong, Edgar H. H.; Tan, Shereen; Guntari, Stefanie N.; Fu, Qiang; Kim, Jinguk; Delalat, Bahman; Blencowe, Anton; Qiao, Greg G.
Abstract : The fabrication of functional and complex multi-layered, multi-compositional, patterned and free-standing polymer films with controllable film properties via catalyst induced cross-linking. Abstract : A new top-down approach to generate stable nanoscale films via catalyst induced cross-linking (CIC) is demonstrated. Polymers with various compositions and bearing pendent norbornene groups (defined as macrocross-linkers) are initially spin-coated onto substrates to form nanometre-thick films; when the films are brought into contact with a catalyst solution, ring-opening metathesis polymerization (ROMP)-mediated cross-linking efficiently occurs to lock the film into place. CIC provides a new paradigm for the fabrication of stable nanoscale films and provides an alternative to traditional methods that use external stimuli ( e.g., heat or light) to trigger film cross-linking. The process requires short cross-linking times (<3 min) to generate covalently bonded and stable nanoscale films. This facile nanoengineering approach allows for the creation of complex multi-layered and multi-compositional patterned films, enables excellent control over film properties such as thickness and swellability, and provides access to nanoscale free-standing polymer sheets. To highlight the versatility of the CIC approach, cross-linked, nanostructured and stratified multi-layered films with tunable film thickness were prepared from norbornene functionalised poly(oligo(ethylene glycol) methacrylate), poly(ethylene glycol) and poly(3-hexylthiophene) macrocross-linkers. CIC proceeds at low catalyst concentrations and allows the catalyst solution to be recycled multiple times, as demonstrated through repetition of 10 individual CIC cycles, making the process economical, scalable and applicable to advanced manufacturing techniques. Furthermore, the technique can be used to produce patterned films through selective exposure of specific regions of the polymer film to the catalyst solution. The CIC approach mediated by ROMP is highly efficient, rapid, robust and versatile, providing new opportunities in film assembly, and complementing existing nanoscale film fabrication methodologies.